Plan de Gestión de Proyecto Para la Implementación del Negocio de Aditivos Para Concreto H Cemex Costa Rica S.A. - Sánchez-Campos, Fernando Alberto (Instituto Tecnológico de Costa Rica, 2015)
This paper proposes a project management plan for the implementation of the admixture’s business for the hydraulic concrete of Cemex Costa Rica S.A., based on the methodological framework for the Professional Administration of Projects, developed by the Project Management Institute. To get an overview of the environment in which the project is developed, the work begins with the analysis of assets and competencies of the organization. Then, an analysis of the processes and requirements necessary to develop it, is done. Under the good practices described in the background knowledge given by the Project Management Institute, the reader will find a reference guide with a propose of analysis that considers the processes and tools needed to manage issues related to the ten knowledge areas.
Proyecto de Graduación (Maestría en Gerencia de Proyectos). Instituto Tecnológico de Costa Rica. Área Académica de Gerencia de Proyectos, 2015.
Keywords: Concreto; Áreas de reconocimiento; PMI; Costo; Calidad